Position Control of Switched Reluctance Motor Using Super Twisting Algorithm. (5th January 2016) - Mufti, Muhammad Rafiq; Butt, Qarab Raza; Iqbal, S.; Ramzan, M.
Abstract : The inherent problem of chattering in traditional sliding mode control is harmful for practical application of control system. This paper pays a considerable attention to a chattering-free control method, that is, higher-order sliding mode (super twisting algorithm). The design of a position controller for switched reluctance motor is presented and its stability is assured using Lyapunov stability theorem. In order to highlight the advantages of higher-order sliding mode controller (HOSMC), a classical first-order sliding mode controller (FOSMC) is also applied to the same system and compared. The simulation results reflect the effectiveness of the proposed technique.